Exercise-Induced Release of Pharmacologically Active Substances and Their Relevance for Therapy of Hepatic Injury - Schon, Hans-Theo; Weiskirchen, Ralf (Frontiers in Pharmacology, 2016)
Chronic liver disease features constant parenchymal injury and repair together with an increasing hepatic impairment, finally leading to fibrosis and cirrhosis and a heightened risk of hepatocellular carcinoma. Closely related to the rise in obesity, the worldwide prevalence of nonalcoholic fatty liver disease, the most common form of chronic liver disease, has reached an epidemic dimension and is estimated to afflict up to 46 percent of the general population, including more than one out of three U.S. citizens. Up to now there is no effective drug treatment available, which is why recommendations encompass both exercise programs and changes in dietary habits. Exercise is well-known for unleashing potent anti-inflammatory effects, which can principally counteract liver inflammation and chronic low-grade inflammation. This review article summarizes the underlying mechanisms responsible for the exercise-mediated anti-inflammatory effects, illustrates the application in animal models as well as in humans, and highlights the therapeutic value when possible. Based on the available results there is no doubt that exercise can even be beneficial in an advanced stage of liver disease and it is the goal of this review article to provide evidence for the therapeutic impact on fibrosis, cirrhosis, and hepatocellular carcinoma and to assess whether exercise might be of value as adjuvant therapy in the treatment of chronic liver disease. In principle, all exercise programs carried out in these high-risk patients should be guided and observed by qualified healthcare professionals to guarantee the patients' safety. Nevertheless, it is also necessary to additionally determine the optimal amount and intensity of exercise to maximize its value, which is why further studies are essential.